Edukasi Bahaya Hipertensi Pada Ibu Hamil Di Puskesmas Simalingkar - Rahmawani Fauza (Cybernetics: Journal Educational Research and Social Studies, 2022)
Introduction High blood pressure of pregnant women (hypertension) can cause intrauterine fetal growth disorders which of course will have an impact on birth weight. The number of maternal deaths by province in 2018-2019 decreased from 4,226 to 4,221 maternal deaths in Indonesia based on reports. In 2019, the most common causes of maternal death were bleeding (1,280 cases), hypertension in pregnancy (1,066 cases), infection (207 cases). During 2006 to 2019 the coverage of health services for K4 pregnant women tends to increase. When compared with the target of the Ministry of Health's 2019 Strategic Plan (Renstra) which was 80%, the 2019 achievement had reached the target of 88.54%. (Ministry of Health RI, 2019) Objective: Researchers provide counseling to pregnant women about the dangers of hypertension to pregnancy, this aims so that mothers can avoid, or prevent the occurrence of hypertension, for mothers who have a history of hypertension, are expected not to aggravate the situation by avoiding things that can worsen the mother's condition such as stress. , and maintain diet and adequate sleep patterns Methods: The method used in this study is a quantitative method and a qualitative method, where the researcher explains the incident through data collection focused on numerical data, as well as by interviewing respondents and providing counseling to respondents.